Poncirin attenuates CCL4-induced liver injury through inhibition of oxidative stress and inflammatory cytokines in mice - Hadayat Ullah; Ashrafullah Khan; Muhammad Waleed Baig; Naseem Ullah; Naveed Ahmed; Muhammad Khalid Tipu; Hussain Ali; Salman Khan (BMC, 2020)
Abstract Background In the present study, the poncirin which is flavonoid-7-o-glycosides (isolated from the Poncirus trifoliata) in nature was evaluated against the Carbon tetra chloride (CCL4)-induced liver injury. The poncirin have been reported for various anti-inflammatory, analgesic activity etc. Based on the previous studies it was anticipated that the poncirin will ameliorate CCL4-induced liver injury. Methods The CCL4-induced acute and chronic liver injury model (albino BALB/c mice) was used. Following the induction of the liver injury various parameters such as food and water intake, body weight and weight to dry ratio changes were assessed. Furthermore, various hematological, biochemical parameters and histological studies such as hemotoxylin and eosin (H and E) staining were performed. The poncirin treatment was also evaluated against the pro-inflammatory cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) using enzyme link immunosorbant assay (ELISA). The Swiss Target prediction software was used to investigate interaction of the poncirin on the various hepatic enzymes. Results The poncirin treatment markedly improved the behavioral parameters such as food and water intake. The liver weight variation was attenuated and total body was improved markedly. The hematological and biochemical parameters were significantly improved compared to the CCL4 treated groups. The anti-oxidants were induced, while oxidative stress markers were reduced promisingly. The H and E staining showed that poncirin treatment significantly improved the histology of liver compared to the CCL4 treated group. Furthermore, the poncirin treatment also evidently decreased the inflammatory mediators. Conclusions The poncirin treatment showed marked improvement in behavioral, biochemical and histological parameters following CCL4-induced liver injury. Additionally, the poncirin treatment also markedly improved the antioxidant enzymes, attenuated the oxidative stress markers and inflammatory cytokines.